Addressing Sunshine State Standards in Elementary School Teacher Professional Development Workshops - Jennifer A. Seitz; Martha C. Monroe; Kimberly O. Thurman (EDIS)
FOR-220, a 6-page illustrated fact sheet by Jennifer A. Seitz, Martha C. Monroe, and Kimberly O. Thurman, use Project Learning Tree (PLT) workshops as an example of how anyone conducting professional development workshops can improve attendance and enhance program use by public school teachers by identifying and advertising the Sunshine State Standards (SSS) that the workshops address. Published by the UF School of Forest Resources and Conservation, May 2009.